The effects of clipping, nitrogen source and nitrogen concentration on the growth responses and nitrogen uptake of an east african sedge - Ruess, R W; McNaughton, S J; Coughenour, M B (Oecologia, 1983)
Kyllinga nervosa Steud., a sedge from the Serengeti short-grass plains, was subjected to a balanced factorial experiment which included unclipped plants and plants clipped weekly to a 5 cm height, nitrogen supplied as either nitrate or ammonium and three nitrogen concentrations. Tillering rates, green leaf nitrogen, and both green leaf weight and biomass investment in green leaf production increased with nitrogen concentration. Low nitrogen conserved investment in crown production and resulted in adjustments for nitrogen acquisition by increasing biomass allocation to root production. Nitrate nutrition stimulated green leaf weight, tillering rate, nitrogen redistribution and both crown and root nitrogen. Ammonium nutrition increased nitrogen uptake, total plant nitrogen accumulation, reproduction, litter weight and nitrogen loss to decomposers. Clipping increased investment in green leaf production at the expense of stem, root, crown and flower production. Compensatory green leaf production in response to clipping occurred only when plants were grown in ammonium. Clipping stimulated uptake rates of both ammonium and nitrate, and therefore total plant nitrogen accumulation. Results suggest a balanced utilization of both nitrate and ammonium may be necessary for optimal growth in this species.